DOS NUEVOS CUADROS DE SENÉN VILA EN ORIHUELA - López Martínez, Mª Cruz (Imafronte, 1993)
Two new paintings by Senén Vila found in Orihuela, un Inmaculate Conceptión (presently in the Museum of the Holy Week) and a Saint Francis Xavier (in the convent of Saint John the Baptist, of the Order of Saint Clare), corroborate his stay in the city and his influence on the 17th, century painting of the zone (un example of which is the important painting in the refectory of the College of Saint Dominic). The mentioned paintings enlarge the rich production of the artist preserved in Orihuela and confirm his high pictorial quality.